STUDI PEMBUATAN KUAH LAKSAN INSTAN DENGAN PERBANDINGAN BUBUK SANTAN DAN UDANG REBON SUNGAI - Oktarini, Dwi; Suyatno, Suyatno; Yani, Ade Vera (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2017)
This Study of Making Instant Laksan Soup by Coconut Milk and the Powder of River Small Shrimp Comparison", using Completely Randomized Design (RAL) which were arranged in nonfactorial with coconut milk and the powder of river small shrimp comparison treatment factor with five levels factor treatment and repeated 4 (four) times. The parameters were observed in this study, includes chemical analysis of water content, fat content and protein content. Organoleptic tests include aroma, flavor, and color. The highest water content is in F0 treatment (coconut milk 60%: the powder of river small shrimp 0%) with an average value of 4.45%. The highest fat content contained in F0 treatment (60% coconut milk: the powder of river small shrimp 0%) with an average value of 2.74%. The highest protein content in F4 treatment (40% coconut milk: the powder of river small shrimp 20%). The value of the highest pleasure levels of instant laksan soup color was found in the F0 treatment (60% coconut milk: the powder of river small shrimp 0%) with an average value of 4.26 (preferred criteria). The value of the highest pleasure levels of instant laksan soup aroma was found in the F2 treatment (coconut milk 50%: the powder of river small shrimp 10%) with an average value of 4.13 (preferred criteria). The value of the highest pleasure levels of instant laksan soup flavor was found in F2 treatment (50% coconut milk: the powder of river small shrimp 10%) with an average value of 4.04 (preferred criteria).